Social movement among tribals: a sociological analysis of Bhils of Rajasthan. - Jain,Prakash Chandra (New Delhi, 1991)
The present study deals with the Social Movements among Bhils of Southern Rajasthan, who constitute the third largest group of tribals in the country. The enquiry provides new insight in the tribal social movements. The study reveals a critique to the historians' analysis of Bhil's Social Movements and their approach char acterised by feudal attributes has been severely condemned. The social movements currently prevalent among the Bhils, i.e., Bhagatism and Christianity have been subjected to this sociological analysis. The author vehemently argues that these cultural movements should not be misunderstood in the sense that the Bhils are becoming Hindus or Christians. His basic argument is that the Bhils are in search of their cultural identity in the regional society by accepting the present norms and values in the process of new social formation. The author's analysis of Bhils' social structure in the context of social movements makes a new breakthrough in the present sociological literature.
Keywords: Tribes Rajasthan